2011
DOI: 10.1002/gps.2687
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for psychosocial interventions in dementia care: a European survey and comparison

Abstract: Objective: The effectiveness of psychosocial interventions in treating people with dementia and their carers is increasingly emphasised in the literature. Dementia guidelines should summarise the scientific evidence and best practice that is currently available, therefore, it should include recommendations for psychosocial interventions. The aims of our study were (1) to collate dementia guidelines from countries across Europe and to check whether they included sections about psychosocial interventions, and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 69 publications
(52 reference statements)
2
42
0
1
Order By: Relevance
“…It appears that although positive outcomes can be identified when managing behavioral disturbances, it is unclear what causes results to be maintained over time. Recent research has identified the need for strong evidence of their effectiveness [46]. Lawrence et al (2012) showed the benefits of these interventions on QoL and recommend individual psychosocial interventions with a specialist [47].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that although positive outcomes can be identified when managing behavioral disturbances, it is unclear what causes results to be maintained over time. Recent research has identified the need for strong evidence of their effectiveness [46]. Lawrence et al (2012) showed the benefits of these interventions on QoL and recommend individual psychosocial interventions with a specialist [47].…”
Section: Discussionmentioning
confidence: 99%
“…If a generic palliative care guideline was not available then raters chose the most widely used cancer care guidelines. This method was successfully used in a review of European guidelines for psychosocial interventions in dementia 11. If members of our network were unable to assist or, a country was not involved in the network, we identified leaders in palliative care through the European Association for Palliative Care (EAPC) or through personal contacts.…”
Section: Methodsmentioning
confidence: 99%
“…Programs to increase physicians' knowledge about existing strong evidence based programs would greatly increase the likelihood that they will be used-either alone or alongside other treatments for both patients and caregivers (Vasse et al, 2012). For example, in India, raising awareness of the progression of dementia is sorely needed as physicians lack knowledge about how to assess and treat dementia patients at the various stages of the disease.…”
Section: What Makes Evidence-based Programs Successful?mentioning
confidence: 99%
“…In addition, creating awareness at the general societal level (via media such as radio, television and social network sites) will bring about ways to improve the quality of life for dementia patients and their caregivers. • Third, governments and philanthropic organizations, especially in countries with strong cultural traditions of family care (Vasse et al, 2012) need to make significant investments in development and dissemination of new nonpharmacological treatments and should support research efforts to improve evidence for their effectiveness. Research needs to span basic science, medical, clinical, epidemiological as well as psychological, social and environmental interventions and must include interventions for caregivers.…”
Section: Implications Of Current State Of Knowledge For Futurementioning
confidence: 99%